Perbedaan Luaran Maternal pada Pasien Preeklampsia dengan Covid-19 dan Tanpa Covid-19 - Veronica Shania Aprillia; Ferry Armanza; Rahmiati Rahmiati (Homeostasis, 2022)
Abstract: Preeclampsia is a pregnancy complication characterized by the onset of high blood pressure that occurs after 20 weeks of pregnancy. Pregnant women are prone to infection by COVID-19 and the risk of pregnancy complications. These causes can effect complications in maternal outcomes such as HELLP syndrome, pulmonary edema, acute kidney failure, and eclampsia, which will affect methods of childbirth and even cause maternal death. The purpose of this study is to determine the differences in maternal outcomes of preeclampsia with COVID-19 and without COVID-19.This study is an analytical observational with a retrospective approach using chi-square test and fisher exact test as an alternative, using secondary data from medical records of preeclampsia patients with COVID-19 and without COVID-19 at RSUD Ulin Banjarmasin for May 2020 – April 2021. The results showed there were differences in outcomes of methods of childbirth (p=0,001) while there were no differences in outcomes of HELLP syndrome (p=0,554), eclampsia (p=0,960), kidney failure (p=0,139), pulmonary edema (p=0,730), and maternal death (p=0,521). From those results, it can be concluded that there were differences in outcomes of methods of childbirth and there were no differences in outcomes of HELLP syndrome, eclampsia, kidney failure, pulmonary edema, and maternal death in preeclampsia patients with COVID-19 and without COVID-19. Keywords: maternal outcomes, preeclamsia, COVID-19 Abstrak: Preeklampsia adalah gangguan kehamilan ditandai hipertensi setelah 20 minggu kehamilan. Ibu hamil rentan terjangkit COVID-19 dan berisiko komplikasi kehamilan. Gangguan ini mengakibatkan terjadinya luaran maternal seperti sindrom HELLP, edema paru, gagal ginjal akut, eklampsia, mempengaruhi metode persalinan bahkan kematian ibu. Tujuan penelitian ini untuk mengetahui perbedaan luaran maternal pasien preeklampsia dengan COVID-19 dan tanpa COVID-19. Penelitian ini bersifat observasional analitik dengan pendekatan retrospektif menggunakan uji chi-square dan uji fisher exact sebagai alternatif, menggunakan data sekunder dari rekam medik pasien preeklampsia dengan COVID-19 dan tanpa COVID-19 di RSUD Ulin Banjarmasin periode Mei 2020 – April 2021. Hasil penelitian menunjukkan perbedaan luaran metode melahirkan (p=0,001), sedangkan luaran sindrom HELLP (p=0,554), eklampsia (p=0,960), gagal ginjal (p=0,139), edema paru (p=0,730), dan kematian (p=0,521) tidak terdapat perbedaan. Kesimpulan penelitian terdapat perbedaan luaran metode melahirkan dan tidak terdapat perbedaan luaran sindrom HELLP, eklampsia, gagal ginjal, edema paru dan kematian pada pasien preeklampsia dengan COVID-19 dan tanpa COVID-19. Kata-kata kunci: luaran maternal, preeklampsia, COVID-19